Institutionalizing effective grant funded programs: A success story - Madhura Kulkarni; Bethany V Bowling; Maureen Doyle; Diana McGill (Academic Chairpersons Conference Proceedings, 2018)
As budgets tighten, universities are increasingly struggling with questions of how to institutionalize and sustain successful grant-funded programs. Creative approaches to leveraging existing infrastructure and resources can make it possible. Here, we present our experiences and approaches that could benefit those seeking to institutionalize effective pilot or grant-funded programs.
Keywords: Institutionalization; Sustainability; Academic Centers; STEM; Undergraduate